2019
DOI: 10.1111/jen.12656
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of Telenomus tridentatus (Platygastroidea: Scelionidae): An unwanted parasitoid

Abstract: The microbiota of Hymenoptera is limited to certain bacterial species that vary according to the habitat and diet; however, the bacterial populations are not known in Telenomus tridentatus Johnson & Bin, an egg parasitoid of agricultural importance. We determined the microbiota composition of adults of T. tridentatus using next‐generation sequencing technologies. We found the presence of the Phylums Proteobacteria, in greater proportion followed by Actinobacteria and Firmicutes, respectively. The most abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Additionally, relative abundance of Staphylococcus was above 0.5% only in one replicate out of three (Table S5) and it did not appear in the MR microbiome. This bacterium has been repeatedly reported as a gut microbe in insects (e.g., wasp, 47 parasitoid wasp, 43 aphids and moths, 48 Beetles, 49 termites 50 ). No substantial association between arthropods and Carnimonas has been previously reported (although it was found in surveys of surroundings of honeybees 51,52 ), and since our attempts to detect it by diagnostic PCRs have failed, we concluded that it was a single case of contamination or a ‘by‐ passer’.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, relative abundance of Staphylococcus was above 0.5% only in one replicate out of three (Table S5) and it did not appear in the MR microbiome. This bacterium has been repeatedly reported as a gut microbe in insects (e.g., wasp, 47 parasitoid wasp, 43 aphids and moths, 48 Beetles, 49 termites 50 ). No substantial association between arthropods and Carnimonas has been previously reported (although it was found in surveys of surroundings of honeybees 51,52 ), and since our attempts to detect it by diagnostic PCRs have failed, we concluded that it was a single case of contamination or a ‘by‐ passer’.…”
Section: Discussionmentioning
confidence: 87%
“…Only a handful of papers reported the characterization of parasitoids' microbiome by molecular methods 43–46 . In those, a diverse community of bacteria was found, most of which was attributed to environmental microbes, associated with gut activity or transient.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of bacterial diversity in Nasonia have shown the presence of Proteobacteria (74.4%), Actinomyces (15.7%), and Firmicutes (9.5%) [10]. Ramírez-Ahuja et al [28] reported the microbiomes of Telenomus tridentatus (Platygastroidea: Scelionidae) (Proteobacteria, Actinobacteria, and Firmicutes), which were similar to the results obtained at the phylum level.…”
Section: Discussionsupporting
confidence: 62%